Response to commentaries by Schmidt and Kaplan, Penhune, Hickok and Theofanopoulou on “Beat-based dancing to music has evolutionary foundations in advanced vocal learning.” - Aniruddh D. Patel (BMC Neuroscience)
Abstract Each commentary on my article raises important points and new ideas for research on rhythmic processing in humans and other species. Here I respond to points concerning the role of social factors in the ontogeny of beat synchronization, the neural connectivity underlying beat synchronization, the evolution of this connectivity, and the mechanisms by which evolutionary changes in the strength of one white matter tract (driven by natural selection) can have knock-on effects on the structure of an adjacent tract.